Exploring the postpartum experiences of first-time parents during the COVID-19 pandemic - Afuang, Carla Maridith D.; Tamayo, Audrey Nicole Y.
This study aimed to explore the lived experiences of first-time parents during the postpartum period amidst the COVID-19 pandemic. Focusing specifically on the roles, challenges and strategies during the pandemic, ten (10) sets of new Filipino parents whose children were born during the pandemic and are currently enrolled in UPCDC were the participants of this study. The study participants were obtained through purposive sampling and were interviewed by the researchers using a semi-structured interview guide, allowing the researchers to further deepen the discussion on topics the parents found relevant to their experience. The collected data underwent coding through thematic analysis to uncover shared meanings that result in themes and categories. Results from the study reflect the abundance of challenges for first-time parents as compared to both roles and strategies based on the frequency and amount of themes generated. An increase in roles among new parents was observed, centering around their self-duty, marital relations, homemaking and childrearing. In terms of challenges, most first-time parents viewed childrearing without prior knowledge as the one which stood out the most. Data also highlighted family and partner support to be the most essential help received by the participants. Overall, this study recommends the establishment of reliable sources of support that can withstand social disruptions brought about by unprecedented events such as the COVID-19 pandemic.